Comparative description of the color lexeme "blue" in the Russian and Armenian languages - Grdzelyan, Ruzan (Bulletin of Yerevan University H: Russian Philology, 2023)
The article is devoted to the relevant in modern linguistics comparativedescription of the semantics of the Russian and Armenian color lexemes "blue" and "կապույտ". The methodology of comparative analysis of these lexemes is conditioned by a number of theoretical prerequisites – an approach to the formation of color semantics as a universal trend, potentially possible in any language; the importance of taking into account the compatibility of color lexemes with the names of natural objects in identifying their semantics; diffuse semantics of color and light; the place of the color term "blue" among the basic eleven color terms. The article carried out a definitional analysis, which revealed differences in the semantic structure of the Russian lexeme "blue" and the Armenian lexeme "կապույտ". Contextual analysis of a large array of texts made it possible to identify the features of the lexical compatibility of the studied words, as well as the semantic components in the structure of their lexical meaning. An analysis of the texts and definitions of color lexemes in explanatory dictionaries, as well as observations of the word usage of their synonyms, made it possible to conclude whether the words "blue" and "կապույտ" are complete lexical parallels, or whether there are discrepancies between them – in lexical and linguocultural semantics, in word usage. The paper also attempts to observe some features of the participation of adjectives denoting color in the organization of the text. An analysis of the texts and definitions of color lexemes in explanatory dictionaries, as well as observations of the word usage of their synonyms, made it possible to conclude whether the words "blue" and "կապույտ" are complete lexical parallels, or whether there are discrepancies between them – in lexical and linguocultural semantics, in word usage. The paper also attempts to observe some features of the participation of adjectives denoting color in the organization of the text. At the end of the article, a summary table of the main words denoting the color blue in Russian and Armenian is presented, conclusions are formulated.